Multiplexed strain sensor for long-distance remote sensing using fiber grating-tuned fiber laser scheme - Kim, S.; Yoon, H.; Lee, S.B.; Choi, S.S.; Lee, B. (CLEO/Pacific Rim 1999 - Pacific Rim Conference on Lasers and Electro-Optics, 1999)
We constructed a fiber laser sensor with two fiber gratings for each sensor array and unidirectional loop cavity. We measured the wavelength shifts of the gratings due to various strains. In spite of the long fiber length of 900 m, high and similar laser power output was obtained. If an interferometric demodulator is used, the sensitivity can be increased, and hence it can be used as a long-distance remote strain sensor system. ？ 1999 IEEE.